(untitled) (Research, Society and Development, 2024)
This integrative review aimed to analyze scientific articles related to dental care that should be adopted by the dentist before, during, and after antineoplastic treatments, as well as to discuss the most frequent oral complications that arise as a result. It is essential to have dental professionals as part of the multidisciplinary team providing care to this patient profile, in order to treat, prevent, delay, or mitigate the emergence of complications from antineoplastic therapy, as these can interfere with treatment continuity and, consequently, influence the case prognosis. For this study, the following descriptors were used: Dentistry; Cancer; Oral complications; Radiotherapy; Chemotherapy. The databases used in the search were: Virtual Health Library (VHL), Scielo, Pubmed, Medline, and Lilacs, where studies between 2014 and 2024 were searched in both English and Portuguese. As a result of the research, 134 articles were found. To select and include these articles in the present study, several steps were taken: first, titles and their respective abstracts were read; then, similar articles, articles that did not address the topic, those not available in English or Portuguese, and finally, articles not available in full and for free were excluded. 115 articles were excluded, leaving 15 articles for full reading. It is concluded that the presence of the dentist as part of the multidisciplinary team is important to adopt dental protocols aiming to prevent, reduce the intensity, or delay possible oral damage that may arise from oncologic therapy, in order to promote a better quality of life for the patient and avoid treatment interruption due to its occurrence.